PENGARUH FASILITAS BELAJAR DI RUMAH TERHADAP MOTIVASI BELAJAR SISWA KELAS V DI SD INPRES BUMI SAGU - Minosri, Ayu; Narayanti, Putu Satya; Kertayasa, I Ketut (STAH Dharma Sentana Sulawesi Tengah, 2025)
The purpose of this study was to determine the effect of home learning facilities on students' learning motivation in class V of SD Inpres Bumi Sagu. The research approach used by the researcher was a quantitative approach with simple linear regression analysis. The population was the total number of class V, which amounted to 31 students. The sampling technique in this study was purposive sampling so that in this study a total of 15 students were used. Based on the research that has been conducted, the results obtained were: 1) The level of home learning facilities for students of SD Inpres Bumi Sagu is high 13.33% (2 respondents), medium 73.33% (11 respondents) and low 13.33% (2 respondents). So it is included in the medium category. 2) The level of learning motivation at SD Inpres Bumi Sagu is high 13.33% (2 respondents), medium 73.33% (11 respondents) and low 13.33% (2 respondents) so it is included in the medium category. 3) From the results of the first hypothesis test, it is known that there is an influence between the variables of home learning facilities and learning motivation. The results of the SPSS test obtained a Sig. value. is 0.019 which is smaller than 0.05, so it can be concluded that there is a significant linear influence between the home learning facilities variable (X) and the learning motivation variable (Y).